A life-course perspective on physical functioning in women - Geeske Peeters; Annette J Dobson; Dorly JH Deeg; Wendy J Brown
Objective To validate Kalache & Kickbusch's model: namely, that functional capacity peaks in early adulthood, then declines at a rate dependent on fitness level until a "disability threshold" is reached. Methods Data came from the Australian Longitudinal Study on Women's Health, which followed three cohorts from 1996 to 2011: a young, a mid-aged and an older cohort (born in 1973-78, 1946-51 and 1921-26, respectively). The Short Form (36) Health Survey was used to measure physical functioning (score 1-100). The disability threshold was the mean physical functioning score in older women requiring assistance with daily activities (62.8). The relationship between age and physical functioning was modelled using spline regression for the entire sample, and by baseline physical functioning quintile and physical activity level. Findings Physical decline quickened with age: 0.05 annual units (95% confidence interval, CI: −0.13 to 0.22) at ages 18-23 years (i.e. no decline); -2.43 (95% CI: −2.64 to −2.23) at ages 82-90 years. Decline was faster in quintiles with lower baseline physical functioning in the younger and mid-age cohorts and in quintiles with higher baseline physical functioning in the older cohort. The disability threshold was reached at a mean age of 79 years, but the range was 45-88 years, depending on baseline physical functioning and physical activity. Conclusion Age and physical decline are not linearly related, as traditionally believed; decline accelerates with age. However, baseline physical functioning, but not physical activity, influences the rate of decline.